2018
DOI: 10.1016/j.aott.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Is volar locking plate superior to external fixation for distal radius fractures? A comprehensive meta-analysis

Abstract: ObjectiveThe aim of this meta-analysis of randomized controlled trials (RCT) and retrospective cohort studies (CS) regarding the use of volar locking plate (VLP) and external fixation (EF) in distal radius fractures was to determine whether there was any evidence that one treatment was superior to the other.MethodsThe meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Electrical databases (PubMed, EMBASE and the Cochrane library) were retrieved to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
2
12
0
1
Order By: Relevance
“…Meta-analyses report that VLP is superior to EF and K-wire in terms of ulnar variance, for all types of radius fractures [14,15]. The ratio of patients with ulnar variance (both positive and negative) was similar in our study groups for all treatment methods.…”
Section: Discussionsupporting
confidence: 58%
“…Meta-analyses report that VLP is superior to EF and K-wire in terms of ulnar variance, for all types of radius fractures [14,15]. The ratio of patients with ulnar variance (both positive and negative) was similar in our study groups for all treatment methods.…”
Section: Discussionsupporting
confidence: 58%
“…The timing of surgery for fractures of the distal radius continues to be debated. The evidence supports the position that the outcomes of locked plating are generally good for these injuries in carefully selected patients, irrespective of age (Azad et al., 2019; Chung et al., 2009; Wang et al., 2018). Functional requirements and early return to function are increasingly seen as key to the physical and psychological recovery of patients and are used to guide treatment decisions (Ikpeze et al., 2016).…”
Section: Discussionsupporting
confidence: 71%
“…Williksen et al [14] used both the Q-DASH and the MAYO scores; however, some surgeons used only Q-DASH scores. [4,[11][12][13] In a meta-analysis, Wang et al [15] reported that higher DASH scores were observed with ORIF, compared to EF. In contrast, one year later, in the meta-analysis of Lee et al, [16] there was no significant difference between the ORIF and EF groups in terms of the Q-DASH scores.…”
Section: Discussionmentioning
confidence: 99%